A novel hybrid interlinking transformer-integrated DFIG wind power and energy storage system with flexible control strategy - Lai, Jinmu; Liu, Yang; Yin, Xin; Wang, Yaoqiang; Hu, Jiaxuan; Yin, Xianggen; Zhou, Keliang (International journal of electrical power & energy systems, 2025)
•This paper proposes a novel DFIG by integrating a hybrid interlinking transformer and energy storage system.•The operating principle and mathematical modeling of HIT-DFIG are analyzed.•A simplified FRT control strategy is presented to enhance the low/high/harmonic voltages ride-through capability of DFIG.•The performance of the HIT-DFIG was verified through simulation and experiments. Double-fed induction generator (DFIG) based wind turbine generator (WTG) demonstrates pronounced sensitivity to the abnormal grid voltages, such as sag, swell or harmonic, which can precipitate disconnections from the power grid due to fault ride-through (FRT) failures. Such disruptions endanger the safe operation of the power system. This paper proposes a novel topology for DFIG-based WTG by integrating a hybrid interlinking transformer (HIT) and energy storage system. The proposed HIT-DFIG system consists of a grid-side converter, rotor-side converter, series converter (SEC), HIT, and direct current energy storage system (DC-ESS). The proposed HIT-DFIG actively adjusts the voltage of the series winding through SEC, achieving active support for the DFIG terminal voltage under grid fault conditions. The DC-ESS provides power support for HIT during the FRT period and has a power smoothing function. Subsequently, the operating principle, and mathematical modeling of HIT-DFIG are analyzed to demonstrate the function of series voltage regulation of HIT. Then, a simplified FRT control strategy is presented, purposed to enhance the low/high/harmonic voltages ride-through capability of DFIG during grid fault scenarios. Finally, the performance of the proposed HIT-DFIG, under diverse operating circumstances such as symmetric and asymmetric grid faults, was verified through simulation and experiments.